Ngaksara: A Mobile Application for Javanese Script Writing Learning and Assessment Media - Nurizal Dwi Priandani; Nimas Ratna Sari; Komang Candra Brata (Journal of Information Technology and Its Utilization, 2026)
Javanese script writing learning was still faced with limited interactive media and delayed assessment feedback in conventional classroom practices. An interactive mobile learning and assessment medium was therefore developed and named the Ngaksara mobile application. A canvas-based Android interface was provided to allow learners to write Javanese characters directly on the touchscreen. Handwritten input was processed through preprocessing and template matching stages, and the similarity between the input image and the standard character template was measured using Manhattan Distance. The assessment result was then converted into a learning category and displayed as immediate feedback for learners. The application used 80 expert-written Javanese character templates as reference templates, while 30 learner handwriting samples were used as evaluation data to assess the agreement between the system output and expert judgment. The system output was highly consistent with expert assessment, and a high level of accuracy was obtained in the handwriting evaluation process. The proposed application was therefore considered useful for supporting Javanese script writing practice and assessment. A simple and lightweight computational approach was also demonstrated, making the application practical for mobile-based educational implementation.